2021
DOI: 10.1002/jmv.26886
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) seroconversion in hematology–oncology patients

Abstract: Since the emergence of SARS‐CoV‐2 in China at the end of 2019, the virus has spread rapidly across the globe leading to millions of infections and subsequent deaths. Although the virus infects those exposed indiscriminately, there are groups in society at an increased risk of severe infection, leading to increased morbidity. Patients suffering from haematological cancers, particularly leukaemia, lymphoma and myeloma, may be one such group and previous studies have suggested that they may be at a 3‐4 times grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This suggests that measuring serological response too soon after SARS‐CoV‐2 infection in HM might lead to an incorrect evaluation of immune response. This probably explains the very low rate of seroconversion reported in 20 HMs (16·6%), tested after 12 days from COVID‐19 15 …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This suggests that measuring serological response too soon after SARS‐CoV‐2 infection in HM might lead to an incorrect evaluation of immune response. This probably explains the very low rate of seroconversion reported in 20 HMs (16·6%), tested after 12 days from COVID‐19 15 …”
Section: Resultsmentioning
confidence: 92%
“…This probably explains the very low rate of seroconversion reported in 20 HMs (16Á6%), tested after 12 days from COVID-19. 15 Figure 1B shows the rate of seroconversion per HM type and specific treatments (more details in Figure S2). We found that serological non-responders were spread evenly across patients with lymphomas, MM and myeloid neoplasms.…”
Section: Covid-19 (78á5%) a Detailed Description Of Patients And Hms Is Available In Tablementioning
confidence: 99%
“…On the other hand, in a series of 21 CLL patients, a seroconversion rate of 67% and a delay in the time of Ab responses were reported [16]. In another study, among 12 patients with HM whose Ab responses to SARS-CoV-2 were measured on average 13 days after symptom onset, only two showed evidence of seroconversion [27]. We have previously reported blunted SARS-CoV-2-specific Ab responses in three immunocompromised individuals, including one with CLL [17].…”
Section: Discussionmentioning
confidence: 95%
“…Smaller case series confirmed the impaired immune response to SARS-CoV-2 in patients with HM and reported a range of seroconversion of 16.6% to 84%. 53,55 Evaluating cellular immune response, Bilich et al 56 Lacking T-cell immunity even in the setting of humoral response was demonstrated in the prospective monocentric study of specific viral immune responses induced by SARS-CoV-2 (COV-CREM) evaluating 39 SARS-CoV-2-infected patients with cancer, including 11 patients with HM. 57 Only 36.4% of patients with HM exhibited T-cell responses against at least 1 of the SARS-CoV-2 proteins (S, M, or N).…”
Section: Introductionmentioning
confidence: 99%